Upper limb rehabilitation robot for physical therapy: design, control, and testing - Akdogan, Erhan (Tubitak Scientific & Technological Research Council Turkey, 2016)
In recent years, the treatment process of patients and disabled people who need rehabilitation and physical medicine has become more effective with the use of new devices and developing technology. The rehabilitation robot is one of the most important developments in new technology. The right therapeutic exercises and the objectivity of the evaluation of the range of motion (ROM; generated torque and muscular activation measurement of the patient) are extremely important factors during treatment. In this study, a lower limb rehabilitation robot was modified and controlled for upper limbs. The retrofitted robot system is able to do passive, active, and active-assistive therapeutic exercises. On the other hand, it performs active-assistive exercises using muscular activation. A web-based human machine interface, which can support home-care service, was developed to control the robotic system. This interface includes a performance evaluation unit, which is able to use not only ROM and torque, but also muscular activation of patients for the assessment of therapy results. Thanks to this system, assessment and physical therapy can be realized by a single robotic system for both upper and lower limbs using physical parameters such as ROM, generated torque, and muscular activation of the limbs. Satisfactory performance of the system is observed in the tests performed with a healthy subject.
Keywords: Rehabilitation robot; electromyography; human-machine interface; therapeutic exercise; assessment; STROKE; SYSTEM; WRIST; Computer Science; Engineering